Impact of activated and resting mesenchymal stem cells on immune responses and gut microbiome and immune responses to gut bacteria in dogs with inflammatory bowel disease - Soontararak, Sirikul, author; Dow, Steven, advisor; Twedt, David, committee member; Lappin, Michael, committee member; Henao-Tamayo, Marcela, committee member (Colorado State University. Libraries, 2019)
Idiopathic inflammatory bowel disease (IBD) is one of the common diseases that causes gastrointestinal tract (GI) disorder and encompasses a group of unknown causes of chronic gastroenteropathies found to have persistent or recurrent GI signs along with intestinal and/or gastric inflammation. Similar to IBD in humans, the pathogenesis of IBD in dogs remains undiscovered, but it is believed to involve an interaction between the abnormal host immune response against intestinal microbiota and predisposing genetic and environmental factors. IBD is mostly incurable with long-term complications despite receiving standard treatments that are typical combinations of food trial, antibiotics, anti-inflammatory and immunosuppressive drugs. However, the therapeutic outcome of medical treatment appears to be multifactorial and inconsistent therapeutic responses ranging from transient recovery to no response have been found. One of the alternative treatments that potentially accelerates therapeutic effects is the use of mesenchymal stem cell (MSC) administration. Therefore, the goal of the research presented in this dissertation was to comprehensively investigate the impact of activated and resting MSCs on immune responses, cells regeneration and gut microbiome for treatment of IBD with a specific emphasis on gaining an improved understanding of the immune responses to the gut bacteria in dogs with IBD. In the first part of the study, we needed to have better understanding of immunopathogenesis in IBD. Although it is not clear what triggers the intestinal inflammations in IBD affected dogs, we hypothesized that the disease may be mediated, in part, by an abnormal immune response directed against intestinal bacteria. We found the substantially greater percentages and overall binding of IgG and IgA with their intestinal bacteria in IBD dogs than healthy dogs, and the primary production of anti-bacterial antibodies occurs locally in the gut rather than systemically. The IgG-binding bacteria triggered an increase of phagocytosis and pro-inflammatory cytokine production by macrophages. Moreover, Actinobacteria (Collinsella genus) was the preferential target for the mucosal IgG immune response to dysbiotic bacteria. We concluded that the mucosal antibody binding to commensal gut bacteria was substantially greater in dog with IBD compared to a healthy, and that the immune response targeted particular bacteria and triggered the pro-inflammatory response in IBD. We noted that the more extensive studies in dogs with IBD and compared to animals with other causes for GI dysfunction may be required. Then, we focused on the use of MSCs as an alternative treatment for IBD in animals and humans. To address this question, we used a mouse model of IBD to investigate the effectiveness of using 2 types of mesenchymal stem cells (induced pluripotent MSC [iMSC] and conventional adipose-derived MSC [adMSC]) for the treatment of IBD. The impact of MSCs on immune responses, cells regeneration and the gut microbiome were evaluated. We found that iMSC and adMSC treatment effects were equivalent on the basis of significantly improving clinical abnormalities and decreasing inflammation inside the gut. Both types of MSC also stimulated a significant increase in intestinal epithelial cell proliferation and amplified intestinal angiogenesis. Furthermore, the abnormal microbiome found in mice with IBD was returned to nearly normal values in terms of complexity and composition in mice with IBD treated with adMSC or iMSC. We concluded therefore that the administration of iMSC enhanced the overall intestinal healing, suppressed inflammation, and microbiome restoration with equal effectiveness as treatment using adMSC in a mouse model of IBD. The future studies in animal model including spontaneous IBD in dog or large scale of clinical trial for long-term follow-up to determine iMSC safety and efficacy is required before clinical translation. Finally, we investigated possible ways to improve the efficacy of mouse and dog MSC treatment by preactivating the MSC with inflammatory cytokines (IFN-g or TNF-a) or TLR agonists (TLR3 or TLR9 agonists). We investigated the response of canine MSCs to the 4 activating stimuli, including measurement of cell surface phenotype and cytokine release. Contrary to previous studies in other species including mouse and man, we found that the pre-activation of dog MSC generally had little effect on either phenotype or function. Therefore, we concluded that the ex-vivo preactivation of canine MSCs by inflammatory cytokines or TLR agonists is not warranted in terms of augmenting the functionality of the cells. We further concluded that dog MSC may be hyporesponsive to preactivating stimuli compared to those of MSC from other species such as mouse and man. Further studies are required for better understanding of the biology of canine MSCs and their responses to immune activation. Overall, the work described in this dissertation has increased our understanding regarding the immunopathogenesis of the IBD in dogs. The studies have also demonstrated the equivalent activity of iMSC and conventional adMSC for treatment of IBD, and also documented a previously undescribed restorative effect of MSC on the intestinal microbiome. These studies also illustrated species specific differences in the responsiveness of MSC to common immune stimuli. These studies provide a robust foundation for further research and hopefully this work can help stimulate new investigations into alternative treatments for IBD in dogs and humans.
Keywords: humoral immune response; inflammatory bowel disease; microbiome; immunoglobulin; canine; mesenchymal stem cell